SMaRT modulation of tau isoforms rescues cognitive and motor impairments in a preclinical model of tauopathy - Muñiz, Javier Andrés; Facal, Carolina Lucía; Urrutia, Leandro; Clerici-Delville, Ramiro; Damianich, Ana; Ferrario, Juan E.; Falasco, Germán; Avale, María Elena (Frontiers in Bioengineering and Biotechnology, 2022)
Tau is a microtubule-associated protein predominantly expressed in neurons, which participates in microtubule polymerization and axonal transport. Abnormal tau metabolism leads to neurodegenerative diseases named tauopathies, such as Alzheimer’s disease and frontotemporal dementia. The alternative splicing of exon 10 (E10) in the primary transcript produces tau protein isoforms with three (3R) or four (4R) microtubule binding repeats, which are found in equal amounts in the normal adult human brain. Several tauopathies are associated with abnormal E10 alternative splicing, leading to an imbalance between 3R and 4R isoforms, which underlies disease. Correction of such imbalance represents a potential disease-modifying therapy for those tauopathies. We have previously optimized a trans-splicing RNA reprogramming strategy to modulate the 3R:4R tau content in a mouse model of tauopathy related to tau mis-splicing (htau mice), and showed that local modulation of E10 inclusion in the prefrontal cortex prevents cognitive decline, neuronal firing impairments and hyperphosphorylated tau accumulation. Furthermore, local shifting of 3R to 4R tau into the striatum of htau mice prevented motor coordination deficits. However, a major bottleneck of our previous work is that local splicing regulation was performed in young mice, before the onset of pathological phenotypes. Here we tested whether regulation of tau E10 splicing could rescue tau pathology phenotypes in htau mice, after the onset of cognitive and motor impairments, comparable to early stages of human tauopathies. To determine phenotypic time course and affected brain nuclei, we assessed htau mice using behavioural tests and microPET FDG imaging over time, similarly to diagnosis methods used in patients. Based on these analyses, we performed local delivery of pre-trans splicing molecules to regulate E10 inclusion either into the medial prefrontal cortex (mPFC) or the striatum at 6-month-old, once behavioral phenotypes and metabolic changes were detected. Strikingly, tau isoforms modulation into de mPFC restored cognitive performance in mice that previously showed mild to severe memory impairment while motor coordination deficit was also rescued after striatal injections. Our data suggest that tau splicing regulation could recover pathological phenotypes, raising promising perspectives for the use of RNA based therapies in tauopathies related to MAPT abnormal splicing.